2020
DOI: 10.1108/emjb-05-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility disclosure and firms' performance in Mediterranean countries: a stakeholders' perspective

Abstract: PurposeThe purpose of this study is to investigate the relationship between corporate social responsibility (CSR) disclosure and firms' operational, financial and market performance (measured in the form of return on assets (ROA), return on equity (ROE) and Tobin's Q (TQ), respectively) in the Mediterranean countries from a stakeholder perspective.Design/methodology/approachResearch is quantitative in nature, based on a cross-sectional and time-series analysis of 203 firms listed in six Mediterranean countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 66 publications
3
67
1
6
Order By: Relevance
“…Despite this, fewer studies focused on the value-creation side of the BM. For example, most studies have focused on economic value (Nielsen et al , 2017), neglecting social and environmental value (Buallay et al , 2020). This represents a significant research gap.…”
Section: Discussion Implications For Research and Practicementioning
confidence: 99%
“…Despite this, fewer studies focused on the value-creation side of the BM. For example, most studies have focused on economic value (Nielsen et al , 2017), neglecting social and environmental value (Buallay et al , 2020). This represents a significant research gap.…”
Section: Discussion Implications For Research and Practicementioning
confidence: 99%
“…This problem may influence firms' future performance, even the planet as a whole. Public awareness of this global issue has required firms to establish environmental regulations and disclose information regarding their commitments towards this vital issue (Nor et al, 2016;Buallay et al, 2020aBuallay et al, , 2020b.…”
Section: Environmental Disclosure and Firms' Performancementioning
confidence: 99%
“…Furthermore, it also increases employees' motivation toward their job responsibility. Buallay et al (2020) adopted the data of 203 firms listed in the six Mediterranean countries. Their findings revealed that CSR activities negatively influenced firm operational performance and had no effect on financial performance.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%